Factors Inhibiting the Collection of BPJS Receivables in Improving Financial Performance (Case Study at Multazam Hospital, Gorontalo): Faktor-Faktor Penghambat Pencairan Piutang BPJS Dalam Meningkatkan Kinerja Keuangan (Studi Kasus Di Rs. Multazam Gorontalo) - Nur Fadila Bahmid; Lisda Van Gobel; Yahya Antu (Institute of Educational, Research, and Community Service, 2023)
This study aims to determine the inhibiting factors in the disbursement of BPJS receivables in improving financial performance at hospitals. Multazam Gorontalo. This type of research is descriptive qualitative approach. The results showed that the inhibiting factor for the disbursement of BPJS receivables in improving financial performance at Multazam Hospital from the HR aspect was that the number of coding officers was only 1 person to verify BPJS patient files and had not recruited due to limited human resources who were experts in coding. The aspect of file completeness, the rate of return of files by BPJS is 5-10% of the total files submitted. Claims that have been revised will be included in new claims submitted to BPJS Health before the 10th. The budget availability aspect for BPJS Health is experiencing a budget deficit caused by participants who are in arrears or do not pay monthly premium contributions. With the disbursement of delayed BPJS patient claim funds, since 2020 the Multazam Hospital has used the SCF program to improve cash flow. It is suggested that the Multazam Hospital needs to recruit coding staff, conduct training related to verification of BPJS patient files (coding system), minimize the return of claim files and complete them in a timely manner, use the integrated BPJS patient claim file application, utilize the supply chain financing (SCF) program from the government effectively and efficiently as possible to maintain cash flow and hospital operations